Penggunaan uchi ni, aida ni, saichuu ni, tochuu de, dalam Kalimat Bahasa Jepang: Kajian Morfosintaksis dan Semantik - Puspita Sari; Sri Iriantini (Universitas Diponegoro, 2025)
This research discusses the use of uchi ni, aida ni, saichuu ni, and tochuu de in Japanese sentences: a morphosyntactic and semantic study. These four structures have similar usage which makes it difficult for foreign learners to understand and apply them, resulting in frequent errors. However, if they are well understood, errors can be minimized. This study will discuss the use of these four structures morphologically, syntactically, and semantically. After that, the similarities and differences will be described. The method used is descriptive qualitative method with library study technique. For the study method, the distributional method is used, and the study technique uses the substitution technique. These four structures have similar meanings but different nuances, in some sentences some can be substituted for each other and some cannot, depending on the use of sentences and conditions. <a href=